Stability analysis and multiple solution of Cu–Al2O3/H2O nanofluid contains hybrid nanomaterials over a shrinking surface in the presence of viscous dissipation - Lund, Liaquat Ali; Omar, Zurni; Khan, Ilyas; Seikh, Asiful H.; Sherif, El-Sayed M.; Nisar, K.S. (Elsevier B.V., 2020)
Researchers are using different types of nanomaterials for the enhancement of the thermal performance of regular fluids such as water, kerosene oil, etc. However, these days, the researchers are more interested in hybrid nanomaterials. The purpose of this communication is to examine the stability analysis of Cu-Al2O3/water hybrid nanofluid over a non-linear shrinking sheet. The hybrid nanomaterials are composed of Cu and Al2O3. These hybridized nanomaterials are then dissolved in water taken as base fluid to form Cu-Al2O3//water hybrid nanofluid. Mathematical analysis and modeling have been attended in the presence of viscous dissipation and suction/injection effects. The governing equations of mathematical models are transformed into self-similar solutions in the form of ODEs by using similarity transformation. Solutions of the non-linear ODEs are created by employing of three-stage Lobatto IIIa formula which is built-in BVP4C function in the MATLAB software. A comparison of the current study has been done with the preceding published literature. The distributions of velocity, temperature profiles, coefficient of skin friction and heat transfer rate are presented graphically and conferred for numerous significant parameters entering into the problem. Results revealed the existence of dual solutions for a certain range of the suction/blowing parameter. Stability analysis is also done in order to obtain dual solutions stability. The smallest eigenvalues suggest that the first solution is stable from the second solution. Hybrid nanomaterials have a high scope toward nurturing our day-to-day life.